[Recensão] WOLFRAM HÖRANDNER, ANDREAS RHOBY, NIKOS ZAGKLAS (eds.), A Companion to Byzantine Poetry (Brill, 2019) - Fonseca, Rui Carlos (2022)
This article is published with Brepols Publishers as a Gold Open Access article under a Creative Commons CC 4.0: BY-NC license. The article is also freely available on the website of Brepols Publishers: https://www.brepolsonline.net/doi/abs/10.1484/J.EUPHR.5.128816 under this same license.